Effective Supervision Model in Supporting The Sustainability of Cooperatives in North Konawe Regency - Irmawati Sastra Dewi Mansyur Piole; Abd. Azis Muthalib; Nofal Supriaddin (PT. Anagata Sembagi Education, 2025)
This research aims to design an effective supervision model in supporting the sustainability of cooperatives in North Konawe Regency. This research design is a model research approach which is also a data analysis design. The informants of this research are 3 employees of the North Konawe Regency Cooperative and MSME Office, consisting of the Head of the Service, the Head of Supervision and Control, the Expert Cooperative Supervisor-first, and 3 Cooperative Members. The type of research uses qualitative descriptive. The data sources in this study consist of primary data sources and secondary data sources. The data collection method uses interview, observation and documentation guidelines. Based on the results and discussion, it can be concluded that the effective supervision model in supporting the sustainability of cooperatives in North Konawe Regency is the Technology and Community-based Supervision Model , which is a cooperative supervision approach that integrates digital technology, such as data management platforms, web-based applications, and accounting software, with the active participation of the cooperative member community.